Expression of SCUBE2 gene declines in high grade endometrial cancer and associates with expression of steroid hormone receptors and tumor suppressor PTEN. (20th September 2013) - Skrzypczak, Maciej; Lattrich, Claus; Häring, Julia; Schüler, Susanne; Ortmann, Olaf; Treeck, Oliver
Abstract: SCUBE2 (Signal peptide-CUB-epidermal growth factor-like domain-containing 2) gene codes for a cell-surface glycoprotein. In breast cancer, SCUBE2 transcript levels are part of important prognostic and predictive gene signatures and are linked to expression of estrogen receptor α (ERα). To elucidate the role of this gene in endometrial cancer, we compared SCUBE2 expression in malignant and normal endometrial tissue specimens. We then examined its correlation with steroid hormone receptors and PTEN and compared it to SCUBE2 expression in breast cancer samples. Expression of SCUBE2 was found to be decreased in G3 endometrial cancer when compared to postmenopausal endometrium or to G1 tumors ( p  < 0.05). In postmenopausal endometrium, SCUBE2 transcript levels were more than twice as high as in premenopausal women. In breast cancer, SCUBE2 expression was found to be notably reduced particularly in ERα-negative G3 tumors. Both in endometrial and breast cancer we observed a significant positive correlation of SCUBE2 transcript levels with expression of ERα, PR and PTEN. Our data suggest that SCUBE2, like in breast cancer, associates with ERα and might have a potential as prognostic or predictive marker in endometrial cancer.